The Literary Testimony of Exile in German-Language Postmigrant Novels: Saša Stanišić’s Herkunft (2019), Dmitrij Kapitelman’s Eine Formalie in Kiew (2021), and Khuê Phạm’s Wo immer ihr auch seid (2021) in the Context of Memory and Remembrance Theories - Jakubski, Michał (Porównania, 2025)
The article analyzes the works Herkunft by Saša Stanišić, Eine Formalie in Kiew by Dmitrij Kapitelman, and Wo auch immer ihr seid by Khuê Pham in the context of post-migrant literature and memory theories. The concepts of identity and memory are examined through the theoretical models of Maurice Halbwachs, Aleida and Jan Assmann, Pierre Nora, and Marianne Hirsch. The analysis of the works highlights the dynamics between adaptation and preservation, as well as the significance of collective and individual memory processes for identity formation in post-migrant societies.